Covid-19 Outbreak and Supply Chain Strategy in Indonesian Government - Riadi, Slamet; Samad, Muhammad Ahsan; Chaeriah Ahsan, Sitti (ExcelingTech, 2020)
Abstract- WHO has deemed the Covid-19 pandemic to be a regional outbreak, Indonesia is one of the pandemic nations. This paper seeks to see the capacity of the world to cope with the global pandemic and the provision of resources through the supply chain policy. Here, we analyse the supply-chain effects of a set of idealized lockdown scenarios, using the latest global trade modelling framework. We find that supply-chain losses that are related to initial COVID-19 lockdowns are largely dependent on the number of countries imposing restrictions and that losses are more sensitive to the duration of a lockdown than its strictness. There are three essential topics in this paper: 1) the sense of urgency; 2) the national government's legislative and structural supply chain policy’s; and 3) the pandemic regional headquarters. The data collection is carried out through scientific journals, online news, reports, and academic forums with public policy and health experts. The findings of this paper indicate that Indonesia is still in difficulty in coping with a global pandemic in the context of the international crisis. Likewise, at the beginning of the outbreak in Indonesia, the system of contact between central and regional representatives seems to be not well organized.